The model of formation of competence for provide the first pre-medical aid in pharmacists - Омельчук, Михайло Анатолійович (ScienceRise: Pedagogical Education, 2016)
In the article is grounded the model of formation of competence for provide the first pre-medical aid in pharmacists and the ways of its realization in the process of study during the cycle “Aid at the urgent states and acute intoxications” as a part of curriculum of postgraduate education of pharmacists-interns, reflected the aim, main approaches, methods, organizational forms of teaching and the complex of pedagogical conditions that guarantee the creation of effective environment for formation of studied competence. There were elucidated the features of teaching of the future pharmacists to provide the first pre-medical aid; according to the competence approach, in correspondence with the separate components of methodical system of the study were elaborated and scientifically grounded the separate components (methods, means, forms) of methodical system of teaching the first pre-medical aid. There were determined the components and levels of formation of competence for provide the first medical aid and acknowledged that the level of evaluation of cognitive and professional-activity components cannot be lower than the middle one